Usability Evaluation of the Online Skill Assessment Tool - Merve Yıldız; Muhammet Berigel; Furkan Kalyoncu; Özlem Özgenç Keleş (Acta Infologica)
This study was conducted to evaluate the usability of the online skill assessment tool which was developed to evaluate the literacy, numeracy, and digital skills of adults with low skill levels. The sample consisted of 14 participants who were between the ages of 18 and 40 and who had graduated from secondary school at most. In the study, the user-based method, in which user experiences are employed, was used, and according to the effectiveness, efficiency and satisfaction criteria determined by ISO 9241-11, the usability of the online skill assessment tool was evaluated. According to the data obtained from the screen recordings, effectiveness was considered as the completion rate of the tasks, and efficiency was considered as the completion duration of the tasks. Satisfaction was also considered as the values obtained from the questionnaire data. The findings indicated that the participants were able to complete most of the tasks and were generally satisfied with the use of the system. Some usability problems were identified as a result of the observations and the detailed examination of the screen recordings. These problems have been a guide for updates to render the system more usable before the system is used by end users.